Morphological and physiological traits for higher biomass production in perennial rhizomatous grasses grown on marginal land. Issue 2 (14th June 2014) - Jones, Michael B.; Finnan, John; Hodkinson, Trevor R.
Abstract A widespread criticism of growing energy crops is that they displace much needed food crops and cause upward pressure on food prices. One solution is the use of marginal land that is unfavourable for food production and is currently underutilized. However, the yield of crops growing on marginal land is reduced because they are subjected to a range of abiotic stresses such as extremes of temperature and rainfall and edaphic factors such as increased soil salinity. Therefore, to achieve acceptable economic returns on the use of this land it will be necessary to, on the one hand improve management practices and on the other to select for plant genotypes which are able to tolerate and potentially overcome the stressful conditions they are exposed to. Here, we review the morphological and physiological traits of perennial rhizomatous grasses that could be modified to overcome these stresses and to maximize biomass production on marginal land. The traits include aspects of crop phenology, canopy and leaf photosynthesis, biomass partitioning, nutrient and water use efficiency and heat, cold and salt tolerance. It is proposed that newly developed biotechnological methods combined with high‐throughput plant phenotyping offer opportunities to rapidly select new genotypes that could achieve economic yields on large areas of marginal land.